Pengelolaan Keuangan Pada UMKM Di Kelurahan Manyaran Kecamatan Semarang Barat Kota Semarang - Astohar Astohar; Maulana Ihsan Yusufi Suyatno; Dhian Andanarini Minar Savitri; Ratna Kase (Institut Teknologi dan Bisnis Semarang, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the drivers of the Indonesian economy. MSMEs have made a significant contribution to improving the economy and also play an important role in growth and employment in Indonesia. Micro, Small and Medium Enterprises (MSMEs) in the Manyaran Village, West Semarang District, are experiencing growth in quantity. Different things are shown by MSMEs which consistently make financial reports, especially micro and small businesses. The problem that arises is that not all MSMEs routinely report MSME performance (operational and financial) so that the financial condition cannot be known early by MSME owners. The dedication method uses lectures, discussions, simulations and questions and answers regarding the benefits and uses of preparing reports. The results of the dedication show that different business units in MSMEs and the educational background of their owners require different ways of communication and delivery. The advice given is to increase the participation of Semarang City Government officials (relevant agencies) through Youth Organizations (youth groups) can be increased again. The results of the dedication show that action is still needed to convince MSMEs regarding the importance of financial reports. Some participants could understand and were enthusiastic in participating in the training. In the future, training and introduction to financial applications related to MSMEs are needed, such as shop books, SIPIK or other applications.